The right of the child conceived by a donor to know his/her origin – Croatian legislation and trends in Europe - Korać Graovac, Aleksandra (European Integration Studies, 2025)
The Convention on the Rights of the Child under Art. 7 para. 1 provides the right of the child to know his or her origin as far as possible. It is not specifically designed for children conceived by donor gametes or embryos, but applies to them as well. The European Convention for the Protection of Human Rights and Fundamental Freedoms (Art. 8) guarantees protection of private and family life. The European Court of Human Rights interpreted that Art. 8 encompasses ‟the right to an identity and to personal development” and finally ruled in Gauvin-Fournis and Silliau v. France that it applies to donor-conceived people and that they have, in principle, a right to know each of their genetic parents. Historically, a donor had the right to privacy and, therefore, remained anonymous; a changed paradigm shifted the focus to persons conceived by the donor’s gametes or embryo. This study analyses the development of representative national legislations that adopt different approaches: those that accept the anonymity of the donor principle, those that accept the non-anonymity principle, and those that accept multiple choices concerning donor’s anonymity. The first has been slowly abandoned in national legislations, however, it continues in liberal and some Central European states. Some states attempt to provide protection, at least by providing choice of non-anonymity/anonymity to the donor. At the European level, Recommendation 2156 (2019) – Anonymous donation of sperm and oocytes: balancing the rights of parents, donors and children of the Parliamentary Assembly of the Council of Europe pushes towards non-anonymity; however, it is not binding. This concept is questionable if the European Union has jurisdiction over such issues, therefore, the 2024 Regulation of the European Parliament and of the Council on standards of quality and safety for substances of human origin (SoHO) intended for human application did not intervene in this area, leaving its regulation to national states. The concluding remarks offer arguments in favour of anonymity and non-anonymity and conclude that legislators should always consider the interests of children and persons conceived, as the state is responsible for the protection of their rights.